Cash Transfers to Poor and Vulnerable Households in Nigeria:: A Critical Analysis of the Gender Mainstreaming Approach - Osondu-Oti, Adaora; Adam, Ibraheem Salisu; Shimang, Shikfu (Journal of Contemporary International Relations and Diplomacy, 2023)
In 2016, the Federal government of Nigeria under President Muhammadu Buhari established the National Social Investment Program (NSIP), including the Cash Transfers (CTs) to tackle poverty in the country and prevent vulnerable households from falling further down the poverty line. The CTs program, known as the Household Upliftment Program (HUP) targeted the poorest of the poor for 6 years (2016-2022) by giving N5000 monthly to “poor” households across the 36 States and the Federal Capital territory. As stated in the National Social Safety Nets Project (NASSP) Manual, cash transfer implementation was guided by gender action plans designed in line with the gender mainstreaming strategy, whose objective is to is to ensure equitable representation and participation in the program by all genders. This paper seeks to address two important research questions; what are the specific ways the gender mainstreaming approach was used in the design of the cash transfer program? Is the implementation of the cash transfers in line with the gender mainstreaming approach?